Maternal and iatrogenic neonatal opioid withdrawal syndrome: Differences and similarities in recognition, management, and consequences. Issue 1 (5th March 2021) - Isaac, Lisa; van den Hoogen, Nynke J.; Habib, Sharifa; Trang, Tuan
Abstract: Opioids are potent analgesics used to manage pain in both young and old, but the increased use in the pregnant population has significant individual and societal implications. Infants dependent on opioids, either through maternal or iatrogenic exposure, undergo neonatal opioid withdrawal syndrome (NOWS), where they may experience withdrawal symptoms ranging from mild to severe. We present a detailed and original review of NOWS caused by maternal opioid exposure (mNOWS) and iatrogenic opioid intake (iNOWS). While these two entities have been assessed entirely separately, recognition and treatment of the clinical manifestations of NOWS overlap. Neonatal risk factors such as age, genetic predisposition, drug type, and clinical factors like type of opioid, cumulative dose of opioid exposure, and disease status affect the incidence of both mNOWS and iNOWS, as well as their severity. Recognition of withdrawal is dependent on clinical assessment of symptoms, and the use of clinical assessment tools designed to determine the need for pharmacotherapy. Treatment of NOWS relies on a combination of non‐pharmacological therapies and pharmacological options. Long‐term consequences of opioids and NOWS continue to generate controversy, with some evidence of anatomic brain changes, but conflicting animal and human clinical evidence of significant cognitive or behavioral impacts on school‐age children. We highlight the current knowledge on clinically relevant recognition, treatment, and consequences of NOWS, and identify new advances in clinical management of the neonate. This review brings a unique clinical perspective and critically analyzes gaps between the clinical problem and our preclinical understanding of NOWS.